1997
DOI: 10.1291/hypres.20.287
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Urinary Sodium Excretion to Blood Pressure, Glucose Metabolism, and Lipid Metabolism in Residents of an Area of Japan with High Sodium Intake.

Abstract: To evaluate the effects of prolonged intake of a high-sodium diet on glucose and lipid metabolism, we examined the relation of daily urinary sodium excretion to blood pressure, glucose metabolism, and lipid metabolism in 140 Japanese adults who lived in a region where the average daily consumption of sodium was high and stable during the past 15 yr; no subject had received any treatment for hypertension or metabolic disorders. Each subject was admitted to our health examination center for 2 d for measurement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Another important finding was the independent association between male gender and increased 24-h sodium excretion. This finding is also not novel and in various studies daily sodium excretion was found to be higher in men then in women [3,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 71%
“…Another important finding was the independent association between male gender and increased 24-h sodium excretion. This finding is also not novel and in various studies daily sodium excretion was found to be higher in men then in women [3,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 71%
“…The INTERSALT study 4 estimated salt intake by 24-h urine collection at 52 centers in 32 countries and showed that the mean daily salt intake was 9.2 g whereas the average value obtained from three Japanese centers was 11.0 g, suggesting that the Japanese have a higher than average salt intake. Residents of Morioka in the Tohoku District of Japan have an even higher salt intake with a mean daily salt intake of approximately 13 g. [5][6][7] This markedly exceeds the daily intake recommended by the Japanese guideline (o6 g), 3 and salt restriction is especially important in areas with high salt intake, such as Morioka. Although the estimation of daily salt intake is important to provide appropriate advice about salt restriction, estimation by interview, the diary method, or 24-h urine collection is inconvenient for general use.…”
Section: Introductionmentioning
confidence: 94%
“…So it is important to clarify the relation between dietary behaviors and blood pressure in the Japanese population. Although studies in various fields have used urinary salt excretion to estimate the dietary salt intake in Japan (17,18), the relationship between urinary salt excretion, which is nearly equal to the dietary salt intake, and the stage of change to a decreased salt intake in the Japanese diet has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%